EVALUATION OF CELLULAR IMMUNE RESPONSE DURING XENOVACCINE THERAPY OF THE PATIENTS WITH STAGE IV OF COLORECTAL CANCER - M. A. Felde; D. M. Samarin; N. A. Niza; A. A. Shishkov; O. V. Poveshenko; E. A. Kashchenko; V. I. Seledtsov; G. V. Seledtsova; V. A. Kozlov (Медицинская иммунология, 2014)
Abstract. Thirty-seven patients with stage colorectal cancer stage IV were subjected to immunotherapy using a polyantigenic vaccine, prepared, basically, from lyzed cells of murine melanoma (B16) and murine carcinoma (LLC) cells. The inducing course of xenovaccine therapy consisted of 10 subcutaneous immunizations (5 injections weekly followed by 5 bi-weekly). Consolidating treatment included monthly vaccinations. Ther xenovaccine therapy was not associated with any serious adverse effects, and did not influence the composition of blood lymphocyte subsets. Significant increase in cellular immune reactions to vaccinal carcinoma-associated antigens occurred in the patients after an inducing treatment, as determined by both skin and antigen-driven blastogenesis test. The overall 2-year survival of thirty-seven stage IV colorectal cancer patients was shown to be significantly better, than in control group (37 clinically comparable patients), with median survival rates of 17 and 7 months, respectively.